2022
DOI: 10.3389/fimmu.2022.940779
|View full text |Cite
|
Sign up to set email alerts
|

Immunological risk factors for sepsis-associated delirium and mortality in ICU patients

Abstract: BackgroundA major challenge in intervention of critical patients, especially sepsis-associated delirium (SAD) intervention, is the lack of predictive risk factors. As sepsis and SAD are heavily entangled with inflammatory and immunological processes, to identify the risk factors of SAD and mortality in the intensive care unit (ICU) and determine the underlying molecular mechanisms, the peripheral immune profiles of patients in the ICU were characterized.MethodsThis study contains a cohort of 52 critical patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 39 publications
0
9
1
Order By: Relevance
“…Jin et al (2022) suggested that chronic obstructive pulmonary disease (COPD) in an elderly study population (age > 60 years; n = 222) was associated with a lower risk of SAE (16.4% SAE vs. 27.8% non-SAE; p -value = 0.047) and lower mortality in the SAE cohort (20% survival vs. 13.9% non-survival; p -value = 0.008) [ 89 ]. This finding is inconsistent with other results described in Table 2 [ 37 , 91 , 92 , 96 ].…”
Section: Possible Role Of Hmgb1 In the Risk Factors For Sae Developmentcontrasting
confidence: 99%
See 4 more Smart Citations
“…Jin et al (2022) suggested that chronic obstructive pulmonary disease (COPD) in an elderly study population (age > 60 years; n = 222) was associated with a lower risk of SAE (16.4% SAE vs. 27.8% non-SAE; p -value = 0.047) and lower mortality in the SAE cohort (20% survival vs. 13.9% non-survival; p -value = 0.008) [ 89 ]. This finding is inconsistent with other results described in Table 2 [ 37 , 91 , 92 , 96 ].…”
Section: Possible Role Of Hmgb1 In the Risk Factors For Sae Developmentcontrasting
confidence: 99%
“…Several studies suggest that increasing age might be an independent risk factor for severe sepsis and SAE development (see Table 1 ) [ 37 , 89 , 90 , 91 , 92 ]. Roughly 60% of ~200,000 septic patients were older than 65 years with 80% case fatality [ 93 ].…”
Section: Possible Role Of Hmgb1 In the Risk Factors For Sae Developmentmentioning
confidence: 99%
See 3 more Smart Citations